A Patient‐Reported Outcome Instrument to Assess Symptom Burden and Predict Survival in Patients with Advanced Cancer: Flipping the Paradigm to Improve Timing of Palliative and End‐of‐Life Discussions and Reduce Unwanted Health Care Costs. (28th September 2018) - Goldberg, Stuart L.; Paramanathan, Dhakshila; Khoury, Raya; Patel, Sharmi; Jagun, Dayo; Arunajadai, Srikesh; DeVincenzo, Victoria; Benito, Ruth Pe; Gruman, Brooke; Kaur, Sukhi; Paddock, Scott; Norden, Andrew D.; et al.
Abstract: Background: Discussions regarding palliative care and end‐of‐life care issues are frequently delayed past the time of usefulness, resulting in unwanted medical care. We sought to develop a patient‐reported outcome (PRO) instrument that allows patients to voice their symptom burdens and facilitate timing of discussions. Subjects, Materials, and Methods: A seven‐item PRO instrument (Cota Patient Assessed Symptom Score‐7 item [CPASS‐7]) covering physical performance status, pain, burden, and depression was administered (September 2015 through October 2016) with correlation to overall survival, correcting for time to complete survey since diagnosis. Results: A total of 1, 191 patients completed CPASS‐7 at a median of 560 days following the diagnosis of advanced cancer. Of these patients, 49% were concerned that they could not do the things they wanted; 35% reported decreased performance status. Financial toxicity was reported by 39% of patients, with family burdens noted in 25%. Although depression was reported by 15%, 43% reported lack of pleasure. Pain was reported by 33%. The median CPASS‐7 total symptom burden score was 16 (possible 0–112). With a median follow‐up of 15 months from initial survey, 46% had died. Patients with symptom burden scores <29 and ≥29 had a 6‐month overall survival rate of 87% and 67%, respectively, and 12‐month survival rates of 72% and 50%. A one‐point score increase resulted in a 1.8% increase in expected hazard. Conclusion: Patients with advanced cancer with higher levels of symptom burden, as self‐reported on the CPASS‐7, had inferior survival. The PRO facilitates identification of patients appropriate for reassessment of treatment goals and potentially palliative and end‐of‐life care in response to symptom burden concerns. Implications for Practice: A seven‐item patient‐reported outcome (PRO) instrument was administered to 1, 191 patients with advanced cancers. Patients self‐reporting higher levels of physical and psychological symptom burden had inferior overall survival rates. High individual item symptom PRO responses should serve as a useful trigger to initiate supportive interventions, but when scores indicate global problems, discussions regarding end‐of‐life care might be appropriate. Abstract : Discussions regarding palliative care and end‐of‐life care issues are often delayed past the time of usefulness, resulting in unwanted medical care. This article reports the results of a multicenter study with a patient‐reported outcome tool used with more than 1, 000 patients with advanced cancers to assess the association between patient symptom burdens distress and overall survival.